2011
DOI: 10.1083/jcb.201106037
|View full text |Cite
|
Sign up to set email alerts
|

Hsp42 is required for sequestration of protein aggregates into deposition sites in Saccharomyces cerevisiae

Abstract: The budding yeast heat shock protein Hsp42 coaggregates with misfolded proteins and may link those aggregates to further sorting factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
418
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(445 citation statements)
references
References 36 publications
22
418
3
2
Order By: Relevance
“…Thus, Btn2p (or associated proteins) recognizes the prion form of Ure2p as distinct from nonprion aggregates of the same protein. Only accumulation of aggregates at the peripheral site requires Hsp42p, and Hsp42p is found to localize at that site (23). We find that Hsp42 is needed for Btn2p overproduction curing, raising the possibility that Btn2p may bring prion aggregates to the peripheral site.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Thus, Btn2p (or associated proteins) recognizes the prion form of Ure2p as distinct from nonprion aggregates of the same protein. Only accumulation of aggregates at the peripheral site requires Hsp42p, and Hsp42p is found to localize at that site (23). We find that Hsp42 is needed for Btn2p overproduction curing, raising the possibility that Btn2p may bring prion aggregates to the peripheral site.…”
Section: Discussionmentioning
confidence: 72%
“…Specht et al found that although benomyl inhibited formation of both peripheral and juxtanuclear aggregate foci, a benomyl-resistant tubulin2 mutant showed the same effect. In contrast, LatrunculinA, which depolymerizes the actin cytoskeleton, inhibited accumulation of aggregates at both sites, but a mutation in actin-1 that prevents LatrunculinA action prevented this action of the drug (23). Thus, the actin cytoskeleton is invovled in IPOD and JUNQ focus formation, distinguishing both from the aggresome.…”
Section: Significancementioning
confidence: 94%
See 2 more Smart Citations
“…Instead, it aggregates in two different subcellular compartments -in the insoluble protein deposit (IPOD), which is close to the vacuole, and the juxtanuclear quality control compartment (JUNQ). In either, aggregated proteins are either refolded by chaperones or degraded by the proteasome (Kaganovich et al, 2008;Specht et al, 2011). Moreover, a new intra-nuclear inclusion (INQ) has been described recently for the deposition of nuclear and cytosolic misfolded proteins (Miller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%